Effect of different enamel matrix derivative proteins on behavior and differentiation of endothelial cells. Issue 7 (July 2015) - Andrukhov, Oleh; Gemperli, Anja C.; Tang, Yan; Howald, Nadia; Dard, Michel; Falkensammer, Frank; Moritz, Andreas; Rausch-Fan, Xiaohui
Highlights We have separated two fractions of EMD proteins. One fraction included proteins with Mr of 8–55 kDa; another fraction proteins with Mr < 8 kDa. We investigated the effect of two EMD fractions on the endothelial cell in vitro. Different biological activity of two EMD fractions was observed.